Effect of procalcitonin-guided therapy on antibiotic usage in the management of patients with chronic obstructive pulmonary disease with acute exacerbation - Randa S. Mohammad; Waleed M. El-Sorougi; Hisham H. Eissa; Abeer S. Mohamed; Khaled E. Hassan (The Egyptian Journal of Bronchology, 2016)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a preventable and treatable disease. In patients with COPD, the clinical manifestations of acute exacerbations due to infectious and noninfectious causes are similar. The differential diagnosis of these two conditions is very important for administering the correct treatment regimen and for avoiding unnecessary antibiotic use, thus reducing the morbidity, mortality, and care-related costs. The aim of this study was to evaluate the diagnostic role of procalcitonin (PCT) and its sensitivity as a marker of bacterial infection in acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients. Patients and methods A total of 53 patients with AECOPD and 30 apparently healthy individuals (control group) were studied. Serum PCT concentrations were measured, and Gram staining of the sputum and sputum culture were performed for the patients with AECOPD. The patients were classified into two subgroups: the bacterial group and the nonbacterial group. The bacterial group included patients with bacterial COPDAE (n=32) and the nonbacterial group included patients with nonbacterial AECOPD (n=21). Results The mean level of PCT in patients of the bacterial group (151.65±38.13) was significantly higher than that of the nonbacterial group (60.16±23.98) and control group (36.03 ±16.52) (P<0.01). Other parameters such as inflammatory markers were also measured in the studied groups (total leukocyte count, erythrocyte sedimentation rate in the first and second hours, and C-reactive protein). There was no significant correlation between serum PCT level and the studied parameters in the bacterial group (P> 0.05), and there was no significant correlation between serum PCT level and the studied parameters in the nonbacterial group (P> 0.05). Pulmonary function testing was done for the studied groups and included forced expiratory volume in 1 s (FEV1)/forced vital capacity (%) and FEV1. The association between serum PCT and FEV1% in the two studied group was not significant (P> 0.05). Conclusion PCT can be used as a marker for differentiation between bacterial and nonbacterial COPDAE and could be used to guide antibiotic therapy and reduce antibiotic abuse in hospitalized patients with AECOPD.